2007
DOI: 10.1111/j.1538-7836.2007.02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of factor VIIa to the endothelial cell protein C receptor reduces its coagulant activity

Abstract: Summary. Background: Endothelial cell protein C receptor (EPCR) binds protein C through its c-carboxyglutamic acid (Gla) domain and enhances its thrombin-thrombomodulin complex-dependent activation. So far, only protein C/ activated protein C has been shown to interact with EPCR. Factor VII (FVII), the coagulation trigger upon tissue factor (TF) interaction, is a serine protease whose Gla domain is highly homologous to the Gla domain of protein C. Objectives: To characterize the binding of FVII/FVIIa to EPCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
135
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 22 publications
17
135
1
1
Order By: Relevance
“…This suggests that EPCR does not induce the necessary essential allosteric conformational changes in FVIIa to enhance its proteolytic activity [3]. However, Lopez-Sagaseta et al [17] reported a noticeable influence of sEPCR on the amidolytic activity of FVIIa, suggesting that the molecule does undergo a structural rearrangement involving its active site. It is interesting to note that sEPCR increased the amidolytic activity of FVIIa even when FVIIa was complexed with TF [17].…”
Section: Cellular Consequences Of Fviia Binding To Epcrmentioning
confidence: 98%
See 3 more Smart Citations
“…This suggests that EPCR does not induce the necessary essential allosteric conformational changes in FVIIa to enhance its proteolytic activity [3]. However, Lopez-Sagaseta et al [17] reported a noticeable influence of sEPCR on the amidolytic activity of FVIIa, suggesting that the molecule does undergo a structural rearrangement involving its active site. It is interesting to note that sEPCR increased the amidolytic activity of FVIIa even when FVIIa was complexed with TF [17].…”
Section: Cellular Consequences Of Fviia Binding To Epcrmentioning
confidence: 98%
“…Thus the binding of FVIIa to EPCR will not have a significant influence on the formation of TF:FVIIa complexes on activated endothelial cells. In light of this, a recent observation that showed blocking of the EPCR binding site on EA.hy926 cells increased the generation of FXa at low concentrations of FVIIa [17] is surprising. However, we are unable to reproduce these data with stimulated HUVEC (unpublished data).…”
Section: Cellular Consequences Of Fviia Binding To Epcrmentioning
confidence: 99%
See 2 more Smart Citations
“…FVIIa binding to EPCR has no influence on the formation of TF-FVIIa complexes on activated endothelial cells (31). However, Lopez-Sagaseta et al (37) recently reported that soluble EPCR dose-dependently inhibited TF-FVIIa activation of FX. They also showed that blocking the EPCR binding site on the endothelial cell surface increased the generation of FXa.…”
Section: Fviia Association With Epcr On Endotheliummentioning
confidence: 99%